Insights into the Ligand Shell, Coordination Mode, and Reactivity of Carboxylic Acid Capped Metal Oxide Nanocrystals. Issue 11 (26th September 2016) - De Roo, Jonathan; Baquero, Edwin A.; Coppel, Yannick; De Keukeleere, Katrien; Van Driessche, Isabel; Nayral, Céline; Hens, Zeger; Delpech, Fabien
Abstract: A detailed knowledge of surface chemistry is necessary to bridge the gap between nanocrystal synthesis and applications. Although it has been proposed that carboxylic acids bind to metal oxides in a dissociative NC(X)2 binding motif, this surface chemistry was inferred from indirect evidence on HfO2 nanocrystals (NCs). Here, a more detailed picture of the coordination mode of carboxylate ligands on HfO2 and ZrO2 NC surfaces is shown by direct observation through solid‐state NMR techniques. Surface‐adsorbed protons are clearly distinguished and two coordination modes of the carboxylic acid are noted: chelating and bridging. It is also found that secondary ligands penetrate the ligand shell and have the same orientation with respect to the surface as the primary ligands, indicating that the ionic or hydrogen‐bonding interactions with the surface are more important than the van der Waals interactions with neighboring ligands. During ligand exchange with amines, the chelating carboxylate is removed preferentially. Finally, it is shown that the HfO2 and ZrO2 NCs catalyze imine formation from acetone and oleylamine. Together with the previously reported catalytic activity of HfO2, these results put colloidal metal oxide nanocrystals squarely in the focus of catalysis research. Abstract : On the surface : Solid‐state NMR spectroscopy shows that entangled carboxylic acid ligands interact with the surface of metal oxide nanocrystals through hydrogen‐bonding and electrostatic interactions (see figure). Tightly bound carboxylic acids are mostly adsorbed on the nanocrystal surface through both the proton and carboxylate. A minor chelating mode is also identified.